Energy efficient asynchronous electric drive of an electromobile - Vorobiov, Bohdan Vitaliyovich (Національний технічний університет "Харківський політехнічний інститут", 2020)
The introductory part of the article describes the relevance of developments in the field of electric vehicles, as well as an economic analysis of the feasibility of using electricity as fuel instead of gasoline on the example of some mass-produced cars. Based on the general requirements for vehicles, a functional diagram of an asynchronous electric drive of an electric vehicle with a supercapacitor battery was built and justified as an intermediate link for the accumulation of electrical braking energy, all elements of the electric drive are described and justified. The parameters of a supercapacitor battery are obtained that can provide the necessary capacity for energy recovery. The optimal structure of the power energy converter was selected, as well as the necessary control algorithms. A mathematical computer model of the electric drive has been built, taking into account all the loads that the electric car experiences during movement, and also allowing modeling the necessary coordinates in various urban cycles of vehicle traffic. A computer simulation of the characteristics of the system was carried out when driving on a horizontal road, as well as when driving from a slope at an angle of 20 °. The characteristics of changes in the voltage on the battery of supercapacitors during regenerative braking are obtained, which allow us to obtain data on the nature of the processes in the battery at each stage of the motion cycle. Transient processes of engine speed and torque are obtained that correspond to the driving influences and the selected control method. The adequacy of the computer model is confirmed and the obtained data are compared with the experimental data presented in the sources. Quantitative indicators of energy recovered in a supercapacitor battery are obtained.

У вступній частині статті описується актуальність розробок у напрямку електромобілебудування, а також проведено економічний аналіз доцільності використання електроенергії в якості палива замість бензину на прикладі деяких серійних автомобілів, що випускаються у наш час. Спираючись на загальні вимоги, що пред'являються до транспортних засобів, була побудована і обґрунтована функціональна схема асинхронного електроприводу електромобіля зі суперконденсаторною батареєю у якості проміжної ланки накопичення електричної енергії гальмування, описані та обґрунтовані всі елементи електроприводу. Отримано параметри суперконденсаторної батареї, які зможуть забезпечити необхідну ємність для рекуперації енергії. Обрана оптимальна структура силового перетворювача енергії, а також необхідні алгоритми управління. Побудовано математичну комп'ютерну модель електроприводу, що враховує всі навантаження, які випробовує електромобіль під час руху, а також дозволяє проводити моделювання необхідних координат в різних міських циклах руху транспорту. Проведено комп'ютерне моделювання характеристик системи, що рухається по горизонтальній дорозі, а також при русі зі схилу під кутом 20°. Отримано характеристики зміни напруги на батареї суперконденсаторів під час рекуперативного гальмування, які дозволяють отримати дані про характер процесів, що відбуваються в батареї на кожному з етапів циклу руху. Отримано перехідні процеси швидкості та моменту двигуна, які відповідають задаючій дії та обраному методу управління. Підтверджено адекватність комп'ютерної моделі електроприводу та отримані дані зіставлені з представленими в джерелах експериментальними даними. Отримано кількісні показники уведеннях в суперконденсаторна батарею енергії.
Енергоефективний асинхронний електропривод електромобілю
Keywords: supercapacitor; regenerative braking; saving energy; суперконденсатор; рекуперативне гальмування; енергозбереження